Peningkatan Literasi Baca Tulis Anak Usia Dini Menggunakan Media Cepica Book di RA Masyitoh 1 Ropoh Kepil Wonosobo - Chasanah, Nikmatul; Khoiri , Akhmad; Munawaroh, Hidayatu (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This thesis aims to: (1) To find out the implementation of Cepica Book media in increasing reading and writing literacy at RA Masyithoh I Ropoh (2) To find out the increase in reading and writing literacy of early childhood using Cepica Book media at RA Masyithoh I Ropoh (3) To find out Supporting and inhibiting factors in increasing early childhood reading and writing literacy using Cepica Book media at RA Masyithoh I Ropoh. This type of research uses Classroom Action Research. Data collection techniques use interview, observation, documentation methods after the data is collected and analyzed using data descriptions, data analysis techniques and conclusions.Based on this research, it can be concluded that (1) To determine the implementation of Cepica Book media on increasing reading and writing literacy at RA Masyithoh I Ropoh (2) To determine the increase in reading and writing literacy of early childhood using Cepica Book media at RA Masyithoh I Ropoh (3) To Knowing the supporting and inhibiting factors in increasing reading and writing literacy in early childhood using Cepica Book media at RA Masyithoh I Ropoh